Cyclodextrin-derived polymer networks for selective molecular adsorption. Issue 79 (22nd September 2020) - Phillips, Bailey; Wang, Chenxu; Tu, Xinman; Chang, Che-Hsuan; Banerjee, Sarbajit; Al-Hashimi, Mohammed; Hu, Wei; Fang, Lei
Abstract : A facile synthetic method is developed to afford cyclodextrin-derived polymer networks that exhibit high selectivity in capturing certain organic compounds in water. Abstract : A facile synthetic method is developed to afford cyclodextrin-derived polymer networks that exhibit high selectivity in capturing certain organic compounds in water. The sustainable and scalable synthesis, together with the highly robust adsorption performance enables efficient removal and/or separation of organic molecules from aqueous solution in a continuous flow system.